If f(x) = 2x^2 +1 and g(x) = 3x-2 what is the value of f(g(x))
1 answer:
Answer:
18x² - 24x + 9
Step-by-step explanation:
To find f(g(x)), substitute x = g(x) into f(x) , that is
f3x - 2)
= 2(3x - 2)²+ 1 ← expand factor using FOIL
= 2(9x² - 12x + 4) + 1 ← distribute parenthesis by 2
= 18x² - 24x + 8 + 1
= 18x² - 24x + 9
You might be interested in
Answer:
Step-by-step explanation:
1. Not a function
2. Function
3. Function
4. Not a function
5. Not a function
6. Function
7. Function
8. Not a Function
9. Function
10. Not a Function
Answer:
3:12
Step-by-step explanation:
Answer:
253.5
Step-by-step explanation:
basically i had the same question so yeah! and im a pro at math
Answer:
1/2, 1/3, 1/4, 1/5, 1/6
Step-by-step explanation:
Answer:
-1
Step-by-step explanation: